2017
DOI: 10.1039/c6ra28497c
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, characterization, and protein-resistance of films derived from a series of α-oligo(ethylene glycol)-ω-alkenes on H–Si(111) surfaces

Abstract: Films on Si(111) were prepared by photo-activated grafting of CH2&#xe001;CH(CH2)m(OCH2CH2)nOCH3 (m = 8, 9; n = 3–7) by using different vacuum conditions. High vacuum produced a higher thickness (40 Å) and <0.8% fibrinogen adsorption (C10EG7). Films were stable even after 28 days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 111 publications
(137 reference statements)
0
1
0
Order By: Relevance
“…Biotin and mannose oligo(ethylene glycol) (OEG) with an azido‐tag was attached to the TMG‐alkyne surfaces, leading to biofunctional OEG‐terminated surfaces that prevents non‐specific adsorption of protein. [ 105 ] It was also demonstrated that the monolayer platform could be functionalized with mannose for highly specific capturing of living target.…”
Section: Functional Surfaces For Efficient Bioconjugationmentioning
confidence: 99%
“…Biotin and mannose oligo(ethylene glycol) (OEG) with an azido‐tag was attached to the TMG‐alkyne surfaces, leading to biofunctional OEG‐terminated surfaces that prevents non‐specific adsorption of protein. [ 105 ] It was also demonstrated that the monolayer platform could be functionalized with mannose for highly specific capturing of living target.…”
Section: Functional Surfaces For Efficient Bioconjugationmentioning
confidence: 99%